PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA POKOK BAHASAN KUBUS DAN BALOK DI KELAS VIII SMP BHAYANGKARI MEDAN - Nurmala Hayati (Journal of Didactic Mathematics, 2020)
This research is in the form of Classroom Action Research (CAR). The subjects in this study were students of class VIII-I of Bhayangkari Medan Middle School and the number of subjects in this class were 40 students. The instrument used to measure students' concept comprehension ability was in the form of filling, with validation and reliability coefficients of the instrument (0.852) for concept comprehension abilities, then the instruments used were observation sheets. The results of the study in the first cycle were obtained as follows: (1) the average understanding of the concept of students 63.90, (2) the percentage of teacher mastery in learning was only 67.85% and (3) students who achieved completeness were only 56.25%. Then proceed to the second cycle, so the results obtained in the second cycle are as follows: (1) the average ability of students' understanding of concepts is achieved as expected by 79.4, (2) the percentage of teacher mastery is also in accordance with the target of 89.75 and (3 ) the percentage of students completeness was 83.75%. Based on the results of the second cycle each aspect has met the minimum completeness criteria so that research is not continued in the next cycle.